2018
DOI: 10.1111/fire.12148
|View full text |Cite
|
Sign up to set email alerts
|

ETF Premiums and Liquidity Segmentation

Abstract: Exchange traded funds (ETFs) provide a means for investors to access assets indirectly that may be accessible at a high cost otherwise. I show that liquidity segmentation can explain the tendency for ETFs to trade at a premium to net asset value (NAV) as well as the life‐cycle pattern in premiums. ETFs with larger NAV tracking error standard deviations (TESDs) tend to trade at higher premiums and the liquidity benefits offered by foreign ETFs and fixed income ETFs are revealed to be the most valuable to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Piccotti (2015) suggested that the positive average premiums for international funds and bond funds might reflect the cost of access that investors are rationally willing to pay in partly segmented markets. In general, the premium distribution is fairly symmetrical, although it has fat tails (Petajisto 2011).…”
Section: Editor's Notementioning
confidence: 99%
“…Piccotti (2015) suggested that the positive average premiums for international funds and bond funds might reflect the cost of access that investors are rationally willing to pay in partly segmented markets. In general, the premium distribution is fairly symmetrical, although it has fat tails (Petajisto 2011).…”
Section: Editor's Notementioning
confidence: 99%
“…Several researchers pursued to identify possible explanations for the exhibited tracking errors by index funds, and Piccotti (2018) showed that ETFs with larger net asset value (NAV) tracking error standard deviations (TESDs) tended to trade at higher premiums, and claimed that TESD had the desirable properties as a liquidity segmentation measure. Saunders (2018), for his turn, analysed 93 country-specific ETFs from 47 different countries and found evidence that the ETF expense ratio was a significant explanatory variable for tracking error, while Akhigbe et al (2020) suggested that tracking error is a determinant for ETFs' likelihood of closure.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Positive effects of the ETFs diffusion have attracted much less attention of researchers and are rarely discussed; they include: extension of the group of investors accessing financial markets, attracted by the features of ETFs such as their diversity or other benefits in relation to the conventional funds (see details in Table 1 ); increased liquidity of the securities whose prices are tracked by passive ETFs due to, above all, improved price discovery mechanism [ 13 , 27 , 28 , 29 , 30 ] or relaxation of the short-sale constraints [ 31 ]. However, there are also studies that provide evidence for the opposite effect, i.e., decreased liquidity (e.g., [ 23 , 32 , 33 ]); potential positive effects of the greater financial openness stemming from the development of cross-listed ETFs or funds offering exposure to foreign assets [ 34 ]. …”
Section: Etfs In the Financial System: Selected Theoretical Issuesmentioning
confidence: 99%
“…increased liquidity of the securities whose prices are tracked by passive ETFs due to, above all, improved price discovery mechanism [ 13 , 27 , 28 , 29 , 30 ] or relaxation of the short-sale constraints [ 31 ]. However, there are also studies that provide evidence for the opposite effect, i.e., decreased liquidity (e.g., [ 23 , 32 , 33 ]);…”
Section: Etfs In the Financial System: Selected Theoretical Issuesmentioning
confidence: 99%